Anticorrelated photoluminescence and free charge generation proves field-assisted exciton dissociation in low-offset PM6:Y5 organic solar cells - Manasi Pranav; Thomas Hultzsch; Artem Musiienko; Bowen Sun; Atul Shukla; Frank Jaiser; Safa Shoaee; Dieter Neher (APL Materials, 2023)
Understanding the origin of inefficient photocurrent generation in organic solar cells with low energy offset remains key to realizing high-performance donor-acceptor systems. Here, we probe the origin of field-dependent free-charge generation and photoluminescence in non-fullereneacceptor (NFA)-based organic solar cells using the polymer PM6 and the NFA Y5—a non-halogenated sibling to Y6, with a smaller energetic offset to PM6. By performing time-delayed collection field (TDCF) measurements on a variety of samples with different electron transport layers and active layer thickness, we show that the fill factor and photocurrent are limited by field-dependent free charge generation in the bulk of the blend. We also introduce a new method of TDCF called m-TDCF to prove the absence of artifacts from non-geminate recombination of photogenerated and dark charge carriers near the electrodes. We then correlate free charge generation with steady-state photoluminescence intensity and find perfect anticorrelation between these two properties. Through this, we conclude that photocurrent generation in this low-offset system is entirely controlled by the field-dependent dissociation of local excitons into charge-transfer states.